A produção acadêmica de um mestrado profissional: uma análise na área de Ensino na saúde - Nascimento, Grazielle Rodrigues de Carvalho (2019)
The present study aimed to analyze the Academic Completion of the Postgraduate Program in Health Teaching (PPES) of the Faculty of Medicine (FAMED), linked to the Federal University of Alagoas (UFAL), from 2011 to 2015 This is a descriptive study with a quantitative approach. We analyzed 81 TACC that were available on FAMED and RIUFAL. To obtain the information, two instruments were built: one for research and one for consolidating the data, which were later condensed and stored in a database in the Excel worksheet. After data collection and analysis, it was possible to investigate in this work Five variables: 1) Production in the Function of the Time of Payment of the Master (FTIM); 2) Profile of the student body; 3) Analysis of the adherence of the TACC to the lines of research; 4) Intellectual production and participation of students in scientific events; and, 5) Educational Products. In the investigation, it was possible to identify that there is a communication failure between the MPES page and the RIUFAL platform, and that the payment time varies between 21 and 49 months. As for the profile of the egress, the majority are female, belonging to the health area and teachers. Regarding the lines of research, there was a predominance of the Curriculum and Teaching-Learning Process in Health Training. As far as the intellectual production was concerned, there were 32 publications made in Periodicals, Annals of Congress, Books and Book Chapters. Of the 81 students, only 17 participated in scientific events. Among the products developed were Outreach Activities. Therefore, in order to better capture the data of the graduates, an instrument for monitoring the egress was developed as an Intervention Product, hosted on the "Portal do Egresso" website, linked to the Program page. This instrument aims to accompany the egress, since its completion captures and stores information regarding their professional development after the completion of the Master. In view of the research carried out, it is concluded that there is a gap in the student's follow-up after completing the Master's program, which may undermine the evaluation of the Program by the Coordination of Personal Improvement of Higher Education (CAPES).